Local buckling characteristic of hollow π-type steel-concrete composite support in hilly-gully region of loess tunnel. (January 2023) - Wang, Zhichao; Cai, Yuancheng; Fang, Yong; Lai, Jinxing; Han, Hongxing; Liu, Jian; Lei, Hao; Kong, Xuguang
Highlights: The deformation and the pressure from surrounding soil affected by the "U" shaped terrain were analyzed. The failure mode, bearing capacity, and deformation characteristics of the arch under different gradient distributed loads were systematically studied. The structural parameters of the steel frame were comprehensively analyzed and optimized. The corresponding anti-buckling measures and concrete pouring scheme were proposed. Abstract: Shallow tunnel can be directly affected by the terrain, and the traditional steel frame is prone to distorting and buckling failure when the tunnel is constructed in a loess region, as it is crisscrossed with hills and gullies. Therefore, the effect of hilly-gully terrain is crucial to the structural stability. The present paper aims to analyze the effect of longitudinal pressure bias on the stability of the π-type Steel-Concrete Composite Support (SCCS) arch. Through the in-situ monitoring of the Dayoushan Tunnel, the deformation and the pressure from surrounding soil affected by the "U" shaped terrain were analyzed. The buckling characteristic, the failure mode, the bearing capacity, and the in-plane and out-plane deformation of the π-type SCCS arch under different gradient distributed (GD) loads were investigated by establishing the nonlinear buckling simulation. The results show that the longitudinal pressure bias had a marked impact on the out-of-plane stability of the π-type SCCS arch. The superposition failure with in-plane local buckling and out-of-plane overall buckling was appeared, the level of gradient magnitude was linearly inversely proportional to the structural bearing capacity, and the out-of-plane deformation of π-type SCCS arch was significantly larger than its in-plane deformation. Also, the stability the π-type SCCS arch with different wall thickness was identified and the corresponding anti-buckling measures for the in-plane and the out-of-plane stability were proposed. This study can further provide reference for the design of loess tunnel support structure in longitudinal pressure bias terrain from the stability perspectives.